2018
DOI: 10.1111/jen.12523
|View full text |Cite
|
Sign up to set email alerts
|

An alternative hypothesis explains outbreaks of conifer‐feeding budworms of the genus Choristoneura (Lepidoptera: Tortricidae) in Canada

Abstract: This alternative hypothesis states that forests attacked by spruce budworms are, for most of the time, nutritional deserts. During these periods, endemic populations persist in scattered “refuges” on a few stressed trees, but this situation changes once trees in a forest become over‐mature and start to senesce. Senescence causes protein in their mature needles to break down at an accelerating rate, releasing higher levels of soluble amino acids into the phloem thereby increasing the quality of food for larval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Similarly, Schramm et al [12] concluded that GST-conjugation of ingested plant compounds occurs, but only partially, and is of limited importance relative to other detoxification mechanisms, including rapid elimination. One possible explanation is that this conjugation is costly, as GSH contains 3 Nitrogen atoms, a nutrient often limiting in herbivores, including the spruce budworm [37]. The sulfur amino acids required for GSH synthesis are particularly low in foliage: for instance, close to 20% of sulfur amino acids ingested by two angiosperm-feeding caterpillars are directed to GSH production [38].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Schramm et al [12] concluded that GST-conjugation of ingested plant compounds occurs, but only partially, and is of limited importance relative to other detoxification mechanisms, including rapid elimination. One possible explanation is that this conjugation is costly, as GSH contains 3 Nitrogen atoms, a nutrient often limiting in herbivores, including the spruce budworm [37]. The sulfur amino acids required for GSH synthesis are particularly low in foliage: for instance, close to 20% of sulfur amino acids ingested by two angiosperm-feeding caterpillars are directed to GSH production [38].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Schramm {{23662 Schramm, K. 2011}} concluded that GST-conjugation of ingested plant compounds occurs, but only partially, and is of limited importance relative to other detoxification mechanisms, including rapid elimination. One possible explanation is that this conjugation is costly, as GSH contains 3 Nitrogen atoms, a nutrient often limiting in herbivores, including the spruce budworm [37]. The sulfur amino acids required for GSH synthesis are particularly low in foliage: for instance, close to 20% of sulfur amino acids ingested by two angiosperm-feeding caterpillars are directed to GSH production [38].…”
Section: Discussionmentioning
confidence: 99%
“…Bark beetles utilize the most suitable trees for breeding first. White [54,55] hypothesizes that raising temperatures enhance phloem nutritional values and therefore beetle outbreaks represent a symptom of degrading forests health, not the main cause of tree mortality.…”
Section: Drivers Of I Typographus Infestation Patternsmentioning
confidence: 99%